2006
DOI: 10.1016/j.bbapap.2005.11.016
|View full text |Cite
|
Sign up to set email alerts
|

The yeast prion protein Ure2: Structure, function and folding

Abstract: The Saccharomyces cerevisiae protein Ure2 functions as a regulator of nitrogen metabolism and as a glutathione-dependent peroxidase. Ure2 also has the characteristics of a prion, in that it can undergo a heritable conformational change to an aggregated state; the prion form of Ure2 loses the regulatory function, but the enzymatic function appears to be maintained. A number of factors are found to affect the prion properties of Ure2, including mutation and expression levels of molecular chaperones, and the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 127 publications
(205 reference statements)
1
27
0
Order By: Relevance
“…Rai et al showed that ure2 mutants have phenotypes similar to those of mutants affected in genes encoding GSTs in S. cerevisiae or Schizosaccharomyces pombe, and they concluded that their results were consistent with a role of Ure2 as a GST (118). Although 1-chloro-2,4-dinitrobenzene is considered an almost universal substrate for those enzymes, a number of them fail to show activity toward it (84), and this is the case for Ure2.…”
Section: Ure2 a Regulator Of Nitrogen Catabolite Repression Exhibitmentioning
confidence: 68%
See 1 more Smart Citation
“…Rai et al showed that ure2 mutants have phenotypes similar to those of mutants affected in genes encoding GSTs in S. cerevisiae or Schizosaccharomyces pombe, and they concluded that their results were consistent with a role of Ure2 as a GST (118). Although 1-chloro-2,4-dinitrobenzene is considered an almost universal substrate for those enzymes, a number of them fail to show activity toward it (84), and this is the case for Ure2.…”
Section: Ure2 a Regulator Of Nitrogen Catabolite Repression Exhibitmentioning
confidence: 68%
“…It has also received much attention due to its relationship with [URE3], a non-Mendelian, nonmitochondrial mutation originally isolated by its effects on nitrogen metabolism in yeast (3). The finding that [URE3] is the prion form of Ure2 (145) has prompted multiple studies to understand the processes that affect prion formation and maintenance (84). The ure2 mutant was generated by Lacroute (83) during a study of genes implicated in the regulation of pyrimidine biosynthesis.…”
Section: Ure2 a Regulator Of Nitrogen Catabolite Repression Exhibitmentioning
confidence: 99%
“…Conversion of Ure2p into the infectious prion form causes a proportion or Ure2p to form high molecular weight amyloid aggregates that prevent the protein from carrying out its normal function in regulating nitrogen metabolism. Hence, [URE3] cells are capable of utilizing poor nitrogen sources while [ure-0] cells are not (Taylor and Wickner 2001;Lian et al 2006).…”
mentioning
confidence: 99%
“…Currently, at least seven different classes of cytosolic GSTs have been defined in fungi: MAK16, EFB␥, Ure2p, Omega, S-glutathionyl-(chloro)hydroquinone reductase, GTT, and etherase-like. Although some isoforms from the Ure2p, Omega, S-glutathionyl-(chloro)hydroquinone reductase, and GTT have been characterized in yeast (11)(12)(13), Aspergillus sp. (14,15), and Phanerochaete chrysosporium (9,16), the etherase-like class has never been studied to date.…”
mentioning
confidence: 99%